A COMPREHENSIVE REVIEW OF THE DEVELOPMENT AND EVALUATION OF FLAME-RETARDANT AND FUNCTIONAL FINISHES FOR CURTAINS AND TEXTILES - Ushma; Guru, Ramratan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Flame retardant finishes are critical for enhancing the fire resistance of textiles and are essential in various applications such as home furnishings, protective clothing, and transportation. This research paper explores the development, application, and evaluation of flame-retardant finishes, focusing on both traditional and innovative approaches. Explores the integration of various functional finishes into curtains, presenting a creative approach to sustainable home décor products. Functional finishes enhance the aesthetics and functionality of curtains and contribute to environmental sustainability. Through a comprehensive study of the mechanisms, types, and performance evaluation methods of flame retardants, this paper aims to provide insights into the effectiveness and sustainability of current technologies. Environmental and health impacts are also addressed, emphasizing the need for eco-friendly alternatives. Experimental results and comparative analysis demonstrate the potential of advanced flame-retardant formulations, paving the way for future research and development.